2008
DOI: 10.1016/j.antiviral.2007.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of inhibitors that interfere with poliovirus replication using a cell-based assay

Abstract: A small molecule library containing 480 known bioactive compounds was screened for antiviral activity against poliovirus (PV) using a cellular fluorescence resonance energy transfer (FRET) assay for viral protease activity. The infected reporter cells treated with the viral replication-suppressing compounds were examined via fluorescence microscope 7.5 h postinfection. Twelve molecules showed moderate to potent antiviral activity at concentrations less than 32 microM during the primary screening. Three compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 25 publications
(26 reference statements)
0
41
0
Order By: Relevance
“…Previous studies have revealed that LPS-induced inflammatory mediator production by macrophages can be attenuated by isoquinoline alkaloids like berberine, and stylopine [31,32]. Lycorine is one of the most common isoquinoline alkaloids and has a variety of pharmacological activities [16][17][18][19]. Nonetheless, little information is available with respect to the molecular mechanisms underlying the anti-inflammatory effect of lycorine.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have revealed that LPS-induced inflammatory mediator production by macrophages can be attenuated by isoquinoline alkaloids like berberine, and stylopine [31,32]. Lycorine is one of the most common isoquinoline alkaloids and has a variety of pharmacological activities [16][17][18][19]. Nonetheless, little information is available with respect to the molecular mechanisms underlying the anti-inflammatory effect of lycorine.…”
Section: Discussionmentioning
confidence: 97%
“…It has received much attention for its various biological effects including antitumor [16], antiviral [17], antimalarial [18], and antiinflammation [19]. Several studies have shown that lycorine induces apoptosis through regulation of the cell cycle in leukemia HL-60 cells and multiple myeloma cell line KM3 [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Lycorine hydrochloride, a plant alkaloid, was previously shown to inhibit poliovirus replication in vitro (17,43) but is known to be highly toxic to mammalian cells. Cycloheximide is also known to inhibit poliovirus replication but is a potent inhibitor of cellular translation (40).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, picornaviral 3C pro is considered an attractive molecular target despite the fact that rupintrivir was not licensed following the clinical trials (8). With the development of high-throughput fluorescence microscopy and its associated image analysis system (9,15,21), this FRET-based biosensor assay represents an ideal platform adaptable for anti-3C pro drug screening. Any candidate compounds from the screening can be further validated by assaying them in HeLa-G3CwtR cells transfected with the 3C pro expression plasmid to rule out those that inhibit virus replication due to their cytotoxic properties.…”
Section: Discussionmentioning
confidence: 99%